Prevention Effort of Stunting By : Brantas Stunting's Video - Johariyah, Johariyah; Apriani, Evy; Septyani, Putri Maretyara (Universitas Malahayati Lampung, 2024)
ABSTRACT Stunting is still an unresolved nutritional problem in Indonesia. Stunting will have a long-term impact on physical, mental, intellectual, and cognitive development. Stunting news in Indonesia ranks fifth in the world. Approximately 5 million of the 12 million boys (38.6%) in Indonesia have a height below the average boys' height in the world. Stunting prevention with monitoring of growth and development, improvement of nutrition and empowerment of the community can be done from the level of basic health care named integrated healthcare center, therefore integrated healthcare center’s (Posyandu) Commnuty Health Volunteers should be well trained and knowledgeable because they will perform early detection of the development and growth of the child. The source of cadres spread throughout the village can be a force in stunting prevention and treatment programmes. Efforts to enhance the knowledge and skills of the cadres in stunting prevention can strengthen the stunting handling powers. This dedication aims to educate cadres in a more attractive way. This dedication is carried out through the provision of stunting education using the video